THE LEVEL OF COGNITIVE, AFFECTIVE AND KONATIVE BANJARMASIN’S PUBLIC BASED ON DEMOGRAPHIC AND PSYCHOGRAFIC IN RESPONDING TO PROHIBITION POLICY THE USE OF PLASTIC AS SHOOPING BAGS - Prihatini Ade Mayvita; Rizka Zulfikar (Program Pascasarjana Universitas Gajayana, 2018)
This study aims to determine the level of cognitive, affective and conative Banjarmasin people in responding to the government's prohibition policy on the use of plastic as a shopping bag based on demographics (gender, age, income, occupation and education level) and psychographics (lifestyle and social level) and whether there is a significance differences in people's cognitive, affective dan conative. This study is a survey research using questionnaires as an instrument. Population and sample used in this study are the Banjarmasin’s public and taken as many as 150 respondents using method. non-purposivesamplingAnalysis techniques were used: (1) qualitative descriptive analysis - quantitative and comparative analysis of the average; (2) The chi-square test to see differences in the behavior of people based on demographic and psychographic and (3) Kruskal Wallis test to see the effects of demographic and psychographic on the level of cognitive, affective and conative Banjarmasin people. This study found that: (1) The level of Banjarmasin’s public cognitive, affective and conative in responding to the prohibition use of plastic as shopping bags are majority in the neutral category; (2) The cognitive aspect is highest tend to be owned by a group of women, aged 41-50 years, government employee, income between Rp 5 million - Rp 9,9 Million, S-2 educated, High life style and lower- upperclass social level.(4) The highest affective aspects tend to be owned by a group of women, aged 41-50 years, goverment employee, income between Rp 5 Million - Rp9.9 Million,S-2 educated, middle lifestyle and upper-middle social level class. (5) the highest connative aspects tend to be provided by a group of women, aged 41-50 years, student / college student, Income between Rp 5 Million - Rp 9.9 Million, S-3 education, high life style and social level of the lower-upper class. (6) In the cognitive and affective, there are no sigificants differences in the average for the whole group demographic and psychographic (7) In the affective, the significant average difference was only found in demographic groups based on job and income while the mean significant difference psychographic groups price found only on psychographic groups based on a social level. (8) The level of cognitive respondent only influenced by the life-style of psychographic variables, afective level is only affected by the psychographic-social level and the level of connative only influenced by demographic variables-education and psychographic variables-social level.